PENGARUH MODEL PEMBELAJARAN FLIPPED CLASSROOM TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI KELAS VIII SMPN 4 LUBUK SIKAPING - Nadia Ulfa Rahmi; Ulfia Rahmi; Meldi Ade Kurnia Yusri; Alkadri Masnur (STKIP Subang, 2025)
This study aims to determine the effect of Flipped Classroom learning on student learning outcomes. This study was conducted at SMP Negeri 4 Lubuk Sikaping. The material used was Emulating the Inspiration and Contributions of Muslim Scientists during the Abbasid Caliphate for Humanity and Civilization with the Flipped Classroom learning model assisted by Google Classroom as a learning medium. This study was a quasi-experimental study. The research sample consisted of 44 students, comprising 22 students in the experimental class and 22 students in the control class, which were determined using purposive sampling. Data collection on student learning outcomes after the treatment was carried out using a posttest instrument. The posttest data showed that the scores in the experimental class were higher than those in the control class. Data analysis using the t- test showed that there was an increase in student learning outcomes after the treatment. The t-test results in the study showed that there was a difference in the average learning outcomes of Islamic Religious Education (PAI) students in class VIII of SMPN 4 Lubuk Sikaping in the 2025/2026 academic year after being taught using the Flipped Classroom model. This shows that the Flipped Classroom learning model has an effect on the Islamic Religious Education (PAI) learning outcomes of eighth-grade students at SMPN 4 Lubuk Sikaping in the 2025/2026 academic year.